UJI KUALITAS BAHAN BAKAR BIODIESEL DARI MINYAK JELANTAH ( PENGGORENGAN PECEL LELE) DENGAN PARAMETER UJI SPESIFIC GRAVITY 60/60 ˚F ASTM D-1298, DISTILASI ASTM D-86, VISKOSITAS KINEMATIK ASTM D-445, FLASH POINT PM ASTM D-93, POUR POINT ASTM D-97 DAN CETANE - Rahma Nuryanti,; Ineke Febrina Anggraini,; Dian Kurnia Sari,; Sonya, (Jurnal Cakrawala Ilmiah, 2023)
Biodiesel refers to one alternative fuel replacing diesel fuel obtained from renewable materials such as vegetable oil / animal fats (cooking oil). Used cooking oil is cooking oil which has been repeatedly used. Repeated use of cooking oil is by cause harm to the consumers. One of the utilizations of used cooking oil is by converting it into biodiesel. This study aims ti find out the process of converting used cooking oil into biodiesel and to investigate the quality of biodiesel produced from converted used cooking oil based on the parameters of Spesific gravity 60/60˚ F ASTM D-1298, distillation ASTM D-86, kinematic viscosity ASTM D-445, flash point ASTM D-93, pour point ASTM D-97, and cetane index ASTM D-4737. The process of making biodiesel from used cooking oil was conducted by two processes, namely esterification dan transesterification. On the process of esterification, ratio of used cooking oil and methanol was 1:2 and H2SO4 as the catalyst. On the process transesterification, on the other hand, the ratio of oil resulted from ester and methanol was 1:2 with NaOH as catalyst. Based on the analysis resul, Spesific gravity 60/60˚ F test showed 0.8562, 0.8569, 0.8569 (on specs), distillation on temperature 90% werw 340, 351 and 341 (on specs), kinematic viscosity resul showed 1,98 (off specs), flash point PM was 130˚ C, and 132˚ C (on specs), pour point result were 15˚ C, 17˚ C and 17˚ C (on specs), and cetane index result showed 51, 52, 51,5 (on specs).